Da nulidade da sentença arbitral e seus efeitos: análise sob a égide das leis 13.105/2015 e 13.129/2015 - Mendes, Mauricio Tartareli (2016)
This term paper it is a study about the arbitration decision annulment of the award, its annulling procedure and its effects. Since the term of the first Federal Constitution, it was already foreseen the arbitration in trade relations, through the 1850 Commercial Code, Civil Procedure Codes and finally to Law n. 9.307/96 (Arbitration Law). Looking forward the analysis of the list of hypotheses to nullify the arbitration decision, in addition to the study of the procedure provided in Arbitration Law and the procedure via motion to deny execution. Which are the ways to obtain the negative constituent sentence and, depending on the procedure adopted or procedural moment or, the reason of the nullify, the interested party shall obtain a judicial provision which can simply determine the adoption or even a decision to invalidate the entire arbitration process, extinguishing all acts with ex tunc effects. With the enactment of Law 13.105/2015 (Civil Procedure Code) and Law 13.129/2015 (Reform of Arbitration Law), the effects of the decision that nullify the arbitration sentence it is decided by the judge, and not by the law, turning the judgement less bureaucratic, leaving to the judge freedom to analyze the case and apply the effect as his conviction